The Establishment of State-Owned-Holding-Company: A State's Controlling Rights Perspective Based on Radbruch's Theory - Disyon, Huta; Gultom, Elisatris; Rahmawati, Ema (Law Review, 2023)
The constitutional basis for the state's role in implementing the national economy is Article 33 of the 1945 Constitution of the Republic of Indonesia. The mandate of Article 33 of the 1945 Constitution regarding the State's Controlling Rights, one of which is realized through the existence of state-owned enterprises (“SOEs”) as one of the business actors in the economy. The expansion of the global economy necessitates the improvement of SOEs, and the government's strategic policy choice is establishing a state-owned holding company (“SOHC”) to strengthen value and efficiency. This research aims to determine how the state's controlling rights in the SOHC scheme relate to three basic legal values identified by Gustav Radbruch, namely justice, certainty, and benefits. Through normative juridical research methods, the approach taken is a conceptual approach and a statutory approach, conducted by researching theory or doctrine and relevant laws and regulations, including Supreme Court and Constitutional Court decisions. The results of this study show that the establishment of a SOHC has, in theory, met Gustav Radbruch's legal objectives of justice, certainty, and benefits. State's controlling rights must be widely understood with authority to formulate policies and actions for regulation, control, management, and supervision. In the management function, state control in the SOHC structure can be protected through special share ownership by the state. However, state control based on a sense of social justice, legal certainty, and benefit-oriented must still respect the principles of GCG in SOEs and do not mean monopolizing all national economic activities.